The Construction of Digital Piety in the Mediatization of Religious Identity in Islamic Content on TikTok - Muhammad Mitra; Erwan Efendi (The Islamic Education and Multiculturalism Foundation, 2026)
This study examines the construction of digital piety within the mediatization process of religious identity in da’wah content on TikTok. The background of this research is based on the increasing use of social media as a space for expressing and representing religious values in digital society. This study employs a descriptive qualitative approach, with data collection techniques including digital observation and documentation of content from religious figures across different faiths. Data analysis is conducted using Robert N. Entman’s framing analysis to explore how religious messages are constructed and interpreted. The results show that digital piety is not only understood as a spiritual practice but also as a representation of religious identity shaped by media logic such as visualization, narrative, and audience interaction. Furthermore, social media serves as a space for interfaith dialogue that promotes tolerance, moral reflection, and the strengthening of faith. In conclusion, digital piety is a symbolic construction formed through the interaction between creators, audiences, and digital platform mechanisms.